DIFFERENCES OF APOLIPOPROTEIN A1 AND APOLIPOPROTEIN B LEVELS IN TYPE 2 DIABETES MELLITUS (T2DM) PATIENTS WITH DIABETIC RETINOPATHY AND WITHOUT DIABETIC RETINOPATHY - hanifah, shabrina; Agni, Angela Nurini; Mahayana, Indra Tri; Suhardjo, Suhardjo; Triyono, Teguh (Indonesian Vitreoretinal Society, 2021)
Introduction Apolipoprotein A1 are antiatherogenic in blood serum and have an anti-inflammatory while Apolipoprotein B describes a protein structure that is potentially atherogenic.. Meanwhile, the inflammatory process plays a role in the diabetic retinopathy process. The aim of this study was to determine whether there were differences in the levels of apolipoprotein A1 and B in diabetic retinopathy patients and without diabetic retinopathy. Methods: This study used a cross sectional design. The subjects of this study were type 2 diabetes mellitus patients with diabetic retinopathy and without diabetic retinopathy at Dr. Sardjito General Hospital from July to September 2020. Subjects consisted of 32 patients in the group with diabetic retinopathy and 31 patients without diabetic retinopathy. The levels of apolipoprotein A1 and apolipoprotein B were analyzed using independent T test. The factors affecting apolipoprotein A1 and apolipoprotein B were analyzed using multiple regression tests. Result: There were no significant differences (p> 0.05) in age, gender, duration of diabetes, HDL, triglycerides, HbA1c, BMI, physical activity, and smoking history. The mean apolipoprotein A1 level in the diabetic retinopathy group was 1.46 ± 0.177 mg / dL higher than the non-diabetic retinopathy group, namely 1.44 ± 0.27 mg / dL (p = 0.699). The mean level of apolipoprotein B in the diabetic retinopathy group was 1.26 ± 0.289 mg / dl higher than the non-diabetic retinopathy group 1.01 ± 0.26 mg / dL (p = 0.001). The mean LDL levels were 162.5 ± 48.38 mmol / L in the diabetic retinopathy group and 127 ± 38.45 mmol / L in the group without diabetic retinopathy (p = 0.012). Conclusion: Apolipoprotein B levels were found to be higher in the group with diabetic retinopathy than in the group without diabetic retinopathy and there was a significant difference between the two assumed due to an atherogenic process in the diabetic retinopathy group. Further research is needed to assess the causal relationship between elevated levels of Apo B and the incidence of diabetic retinopathy by calculating the ratio of apolipoprotein B to apolipoprotein A1. Keywords: Apolipoprotein A1, Apolipoprotein B, Diabetic Retinopathy